2021
DOI: 10.1093/ckj/sfaa268
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap from research to practice for enhanced health-related quality of life in people with chronic kidney disease

Abstract: Improving the health status of people with chronic kidney disease (CKD) through physical activity (PA) or exercise interventions is challenging. One of the gaps in the process of translating the general public PA activity guidelines as well as the CKD-specific guidelines into routine clinical practice is the lack of systematic recording and monitoring of PA and physical function attributes, which can also be used to develop individualized and measurable plans of action to promote PA for health. We aim to prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
0
10
0
1
Order By: Relevance
“…Health-related quality of life (HRQoL) is a multidimensional concept that includes several domains focused on physical, mental, emotional, and social functioning and reflects the impact of health status on individual well-being [ 6 ]. One previous study showed that chronic kidney disease (CKD) affects patients’ HRQoL, so subjects in the more advanced stages of CKD have worse HRQoL than those at the earlier stages of the disease [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Health-related quality of life (HRQoL) is a multidimensional concept that includes several domains focused on physical, mental, emotional, and social functioning and reflects the impact of health status on individual well-being [ 6 ]. One previous study showed that chronic kidney disease (CKD) affects patients’ HRQoL, so subjects in the more advanced stages of CKD have worse HRQoL than those at the earlier stages of the disease [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding HRQoL, even though only three studies were included in the meta-analysis, it showed high evidence of significant impact in two subscales of the SF36, role physical and general health. Previous results have shown a positive impact of HB programs on different cohorts or a positive impact of other modalities of exercise on CKD, such as low-intensity intradialysis exercise (Esteve Simó et al, 2014;Segura-Orti et al, 2021;Shahgholian et al, 2014;Tao et al, 2015), even in older adults with CKD (Junqué Nonoyama et al, 2010). We recommend using the SF36 to measure HRQoL in future studies to facilitate data pooling and adding depression as an outcome measure since its evidence was limited.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise is an effective alternative for renal patients to improve their HRQoL and to help preserve their functional capacity (Segura‐Orti et al, 2021). Hence, it is important to establish exercise programs as an integral part of treatments to help patients avoid functional impairments (Esteve Simo et al, 2015; Howden et al, 2015; Manfredini et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Die Langzeitversorgung von Patient:innen mit chronischen Nierenerkrankungen, Dialyse und nach Nierentransplantation ist bei allen Fortschritten weiterhin defizitär. Die Patient:innen benötigen eine frühzeitige und oft über Jahrzehnte andauernde kontinuierliche multidisziplinäre Versorgung durch Fachärzt:innen für (Kinder‑)Nephrologie und Psychonephrologie unter Einbeziehung von Allgemeinmedizin, Diabetologie, Kardiologie, Shuntchirurgie, Transplantationschirurgie, Pharmakologie, Ernährungsberatung, Fitnessberatung und Rehabilitationskliniken sowie bei Bedarf weiterer Disziplinen ([ 102 ]; Abb. 1 ).…”
Section: Ausblickunclassified